2016
DOI: 10.1111/nph.14039
|View full text |Cite
|
Sign up to set email alerts
|

A novel glucuronosyltransferase has an unprecedented ability to catalyse continuous two‐step glucuronosylation of glycyrrhetinic acid to yield glycyrrhizin

Abstract: Glycyrrhizin is an important bioactive compound that is used clinically to treat chronic hepatitis and is also used as a sweetener world-wide. However, the key UDP-dependent glucuronosyltransferases (UGATs) involved in the biosynthesis of glycyrrhizin remain unknown. To discover unknown UGATs, we fully annotated potential UGATs from Glycyrrhiza uralensis using deep transcriptome sequencing. The catalytic functions of candidate UGATs were determined by an in vitro enzyme assay. Systematically screening 434 pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 65 publications
3
65
1
Order By: Relevance
“…A cluster with soybean's GmUGT73F2 and GmUGT73F4 catalyzing the addition of glucose and xylose, respectively, to an arabinose residue at the C‐22 position of soyasaponins from the A class (Sayama et al ., ) and Medicago 's UGT73F3 involved in the glucosylation of multiple sapogenins at position C‐28 (Naoumkina et al ., ) also included the bean candidate Phvul.003G097300. The last cluster of UGTs involved in triterpenoid biosynthesis including candidates from beans was formed by G. uralensis GuUGAT involved in a two‐step glucuronosylation yielding glycyrrhizin (Xu et al ., ) and three candidates localized in tandem in the same region of chromosome 3 (Phvul.003G046900, Phvul.003G047000 and Phvul.003G047100). Finally, no candidates were identified close to glycoalkaloid‐related proteins, and a group of three candidates (Phvul.008G090500, Phvul.008G090600 and Phvul.008G090900) was localized inbetween the clade of GmSGT2 and GuUGAT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A cluster with soybean's GmUGT73F2 and GmUGT73F4 catalyzing the addition of glucose and xylose, respectively, to an arabinose residue at the C‐22 position of soyasaponins from the A class (Sayama et al ., ) and Medicago 's UGT73F3 involved in the glucosylation of multiple sapogenins at position C‐28 (Naoumkina et al ., ) also included the bean candidate Phvul.003G097300. The last cluster of UGTs involved in triterpenoid biosynthesis including candidates from beans was formed by G. uralensis GuUGAT involved in a two‐step glucuronosylation yielding glycyrrhizin (Xu et al ., ) and three candidates localized in tandem in the same region of chromosome 3 (Phvul.003G046900, Phvul.003G047000 and Phvul.003G047100). Finally, no candidates were identified close to glycoalkaloid‐related proteins, and a group of three candidates (Phvul.008G090500, Phvul.008G090600 and Phvul.008G090900) was localized inbetween the clade of GmSGT2 and GuUGAT.…”
Section: Resultsmentioning
confidence: 99%
“…Common bean has four copies from which only Phvul.010G101800 and Phvul.010G101600 are expressed in the investigated tissues, at particularly higher levels in the seedlings. A cluster with soybean's GmUGT73F2 and GmUGT73F4 catalyzing the addition of glucose and xylose, respectively, to an arabinose residue at the C-22 position of soyasaponins from the A class (Sayama et al, 2012) and Medicago's UGT73F3 involved in the glucosylation of multiple sapogenins at position C-28 (Naoumkina et al, 2010) triterpenoid biosynthesis including candidates from beans was formed by G. uralensis GuUGAT involved in a twostep glucuronosylation yielding glycyrrhizin (Xu et al, 2016) and three candidates localized in tandem in the same region of chromosome 3 (Phvul.003G046900, Phvul. 003G047000 and Phvul.003G047100).…”
Section: Phylogenetic Analysis Of Candidate Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Xu et al . reported that GuUGAT, which corresponds to UGT73B27 in our study but differs from UGT73B27 by one amino acid residue (Leu329 in GuUGAT versus Phe329 in UGT73B27), has catalytic activity to produce glycyrrhizin directly from glycyrrhetinic acid through a continuous two‐step glucuronosylation reaction (Xu et al ., ). The target enzymatic activity was, however, not detected in UGT73B27 in our assay (Figure S9).…”
Section: Discussionmentioning
confidence: 97%
“…Accordingly, many kinds of licorice products had been developed in recent years , . It was reported that famous magnesium isoglycyrrhizinate injection, developed from licorice, reached sales of CNY ¥1.6 billion in China in 2014 . Interestingly, recent study showed that extracts from licorice also had good pharmacological roles in treating prostatitis .…”
Section: Introductionmentioning
confidence: 99%